ANALYSIS OF FINANCIAL MANAGEMENT SKILLS, LIFESTYLE, AND ACADEMIC STRESS AMONG KIP RECIPIENTS - Dina Dwi Oktavia Rini; Dewi Elok Oktaviana Sari (Antis Publisher, 2026)
Objective: This study aims to examine how college students who receive the Indonesia Smart Card (KIP) manage their finances, their lifestyles, and how academic pressures affect them. Method: A qualitative method was used, involving data collection through interviews and observations of four active students from various academic programs. Results: The research indicates that students receiving the KIP demonstrate strong financial management skills, evidenced by their ability to plan fund usage, budget for daily necessities, and control their expenditures. Their lifestyles generally appear simple, frugal, and not wasteful, with a primary focus on educational needs and basic necessities. Meanwhile, academic pressure is perceived differently by each student; some view it as a burden, while others see it as motivation. Pressure from professors and parents is relatively minimal, though it is still felt in some cases. Novelty: This study examines the interrelationship between financial management, lifestyle, and academic pressure among college students receiving the Indonesia Smart Card (KIP) using qualitative evidence from multiple academic programs.